PAKISTAN REJECTED THE COOPERATION WITH SAUDI ARABIA TO INTERVENE IN YEMEN CONFLICT - Win Kenahdi (HI 16 UMY 084, 2016)
*84 Intervention in international politics has become something quite common practice. Intervention is usually made of a country in conflict in other countries with a view to contribute to resolve the conflict. A country to intervene in another country conflict is usually due to the country concerned will be affected either directly or indirectly from the conflict. One of the countries that did the intervention is to Saudi Arabia to the conflict in Yemen.Saudi Arabia, the postscript is an Islamic country Sunni teaching was getting threats from the conflict between Sunni and Syiah in Yemen, which is actually controlled by the Syiah government. Saudi Arabia and then invite some friend countries to take part in his country's agenda Intervention Yemen. Pakistan, an Islamic country that also has a majority of Islamic Sunni teaching, who asked for assistance by Saudi Arabia. Demand Saudi Arabia are not necessarily approved by Pakistan.Pakistan feel need to address their domestic problems in advance that also has some unresolved conflict. In addition, Pakistan has a principle of governance that promotes conflict resolution through diplomacy. Using the theory of foreign policy and national interests concept, the author tried to analyze whether the two situations above are used as an excuse by Pakistan to reject the request of Saudi Arabia in Yemen to intervene. Keywords : Intervention, Foreign Policy, National Interest.